Redox ion exchange membrane and application thereof
Through the new redox ion exchange membrane, chemical reversible reactions are adopted in hydrogen production, the problems of high hydrogen production cost and poor mechanical performance in the prior art are solved, and low-cost and efficient hydrogen production is achieved.
Patent Information
- Application Number
- CN202280092665.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-12-28
- Filing Date
- 2022-12-28
- Publication Date
- 2024-12-13
AI Technical Summary
In the existing hydrogen production technologies, proton exchange membrane (PEM) and anion exchange membrane (AEM) have problems such as high cost, insufficient precious metal abundance and poor mechanical performance, making it difficult to achieve low-cost large-scale hydrogen production.
Using a new redox ion exchange membrane, which transfers protons or anions through chemical reversible reduction and oxidation reactions, rather than relying on traditional chemical ion gradient drives, it is suitable for acidic or alkaline electrolytes, improving the efficiency and reliability of hydrogen production. .
It realizes low-cost and high-efficiency hydrogen production, reduces hydrogen production costs, and meets economic and large-scale hydrogen production needs.
Smart Images

Figure CN119137314A_ABST
Abstract
Description
[0001] CROSS REFERENCE TO RELATED APPLICATIONS
[0002] This application is a PCT international phase application of the U.S. patent application serial number 18 / 090,467 filed on December 28, 2022, which in turn claims priority to the U.S. provisional application serial number 63 / 294,371 filed on December 28, 2021. The entire contents of the two applications are incorporated into this specification by citation. Technical Field
[0003] The present invention relates generally to the production of hydrogen, and more particularly to the use of redox ion exchange membranes for the production of hydrogen. Background Art
[0004] As fossil fuel prices rise, and concerns about climate change associated with the burning of fossil fuels grow, the need for alternative energy sources is growing. Hydrogen is a promising energy source for a green economy. Hydrogen can be produced from water by an electrolysis process, and when burned, the hydrogen produces water again without producing carbon compounds or other undesirable byproducts. However, the electrolysis process is energy intensive, and to the extent that fossil fuels are burned to generate electricity for the electrolysis process, the process does not help the environment.
[0005] As renewable energy sources reach higher grid penetration, hydrogen production from water electrolysis is a promising solution for large-scale time-shifted energy storage and for producing hydrogen for use as fuel. Water electrolysis can be performed in acidic or alkaline environments, respectively, using proton exchange membrane (PEM) electrolysis and alkaline or anion exchange membrane (AEM), which are existing commercialized technologies. Notably, the former has been developed so far for high efficiency but suffers from high cost and insufficient abundance of precious metals, while the latter has been developed so far for robust reliability rather than high efficiency.
[0006] Membrane thickness is important for PEM performance. However, there is a tension between thicker membranes that are more durable in terms of chemical and mechanical stresses and thinner membranes that are more suitable for proton exchange from the anode side to the cathode side. In addition, PEMs degrade in use due to the chemical environment. Intermediate free radicals of peroxides or hydroperoxides play a role in decomposing the PEM during operation. Due to the corrosion of the collector plates, iron and copper ions are formed in the PEM. These ions act as accelerators of the formation of intermediate free radicals, which are harmful to the PEM. In addition, over time, platinum ions from the anode and / or cathode form a layer on the membrane by reduction processes, which reduces performance and durability.
[0007] An example of a PEM is NAFION® from The Chemours Company (Wilmington, Delaware). TM Brand of perfluorosulfonic acid (PFSA) membrane. NAFION TM Branded PEMs have a well-defined porous structure and multiple functional groups, but are expensive, sensitive to contamination and clogging, and generally suffer from the disadvantages described above for PEMs. TM For PEM brands, acid-based electrolytes are used and hydronium ion (proton) exchange occurs across the membrane. TM The exact mechanism of action of branded PEMs is still the subject of research. Figure 1 , showing the NAFION TM Cluster-channel or cluster-network model of the mechanism of action of branded PEM. NAFION TM The brand of PEM has a stable PTFE skeleton with a diameter of essentially The diameter is basically The clusters are interconnected by narrow channels. SO3H is very hydrophilic and attracts water molecules, which tend to solvate the SO3H groups and dissociate protons from the SO3H groups. The dissociated protons "jump" from one acid site to another through water molecules and hydrogen bonding, eventually passing completely through the membrane.
[0008] Like ordinary PEM, NAFION TM The brand's PEM is used for water electrolysis in an acidic electrolyte. Once the electrochemical gas evolution reaction occurs, protons are converted into H2 gas at the cathode and water molecules are oxidized into O2 gas and protons at the anode. TM A proton concentration gradient develops between the two sides of the brand's PEM. This concentration gradient can be converted into a biased chemical potential, driving protons from the anode side through the NAFION TM Brand of PEM reaches the cathode side.
[0009] Anion exchange membrane (AEM) electrolysis is similar to PEM in that it is used for water electrolysis, but in an alkaline electrolyte and the membrane provides ion pathways (H + or OH - ). Unlike PEM, AEM electrolysis eliminates the use of precious metal electrocatalysts and corrosion-resistant building materials. Relatively speaking, period 4 transition metals (e.g., Fe, Co, Ni) can be used to formulate highly efficient electrocatalysts (e.g., 1.0 A / cm at 1.5 V). 2 ), especially when operating at high temperatures.
[0010] In the quest for high ionic conductivity and strong mechanical stability, bipolar AEMs have been developed (e.g., FUMATEC HWT GmbH, Bietigheim-Bissingen, Germany). The purpose of the development of AEM for brands. Figure 2 , AEMs consist of ion clusters in a hydrophobic matrix, where the hydrophobic material causes the ion clusters to aggregate and form interconnected ion channels. AEMs are typically solid polymer electrolytes that contain hydrophobic polymers with attached functional positively charged hydrated ions and surrounding water molecules. The main function of AEMs is to convert OH - Anions are transferred from the cathode to the anode across the membrane. The membrane is based on the interaction of hydrophilic positively charged functional groups with negatively charged OH - The interaction between anions conducts anions.
[0011] Unfortunately, anion exchange membranes (AEMs) suffer from most of the same structural defects and degradation issues as PEMs. The degradation issues of AMEs are even more severe because their polymer backbones and functional groups can be easily affected by OH groups. - and free radical attack. In addition, AEMs are also known for their relatively poor ionic conductivity because OH - The diffusion coefficient is much lower than that of H + ; therefore, a higher ion exchange capacity (IEC) is required. However, higher IEC leads to a sacrifice in mechanical properties due to excessive polymer expansion.
[0012] The Department of Energy has set a goal of reducing the cost of hydrogen production from the current $4 / kg to $1 / kg by 2030. Existing technologies at or near the $4 / kg cost range are unable to achieve the $1 / kg target. Therefore, there is an unmet need for technologies that can economically and easily facilitate continuous, large-scale production of hydrogen. Summary of the invention
[0013] In the present invention, a low-cost hydrogen production system is realized by a novel membrane in which protons or anions are transferred through the membrane by simultaneous chemically reversible reduction and oxidation rather than by conventional chemical ion gradient driven mass transfer. Such membranes can be used with alkaline or acidic electrolytes with high efficiency and reliability.
[0014] A redox ion exchange membrane may include a conductive material and a redox active material associated with the conductive material, the redox active material having reversible oxidation and reduction properties.
[0015] A hydrogen production device may include a cathode, an anode, and a redox ion exchange membrane located between the cathode and the anode, the redox ion exchange membrane having a first surface and a second surface opposite to the first surface.
[0016] A fuel cell device may include a first electrode, a second electrode, and a redox ion exchange membrane located between the first electrode and the second electrode, the redox ion exchange membrane having a first surface and a second surface opposite to the first surface.
[0017] A method of producing hydrogen may include providing a cathode, an anode, and a redox ion exchange membrane between the cathode and the anode, and applying power to the cathode and the anode; wherein the application induces simultaneous reversible reduction and oxidation reactions on opposite sides of the redox ion exchange membrane, thereby releasing H on one side of the redox ion exchange membrane. + . BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a schematic detailed view of a proton exchange membrane (PEM).
[0019] Figure 2 is a schematic detailed view of the anode exchange membrane (AEM).
[0020] Figure 3 is a schematic diagram of a water electrolysis system utilizing a redox ion exchange membrane.
[0021] Figure 3A is a schematic diagram of one embodiment of a redox ion exchange membrane comprising a conductive material as a substantially thin, planar layer with inorganic microstructures on both sides of the layer.
[0022] Figure 3B A schematic diagram of a redox ion exchange membrane comprising a conductive material having a branched structure, with an inorganic microstructure fabricated on the surface of the material.
[0023] Figure 3C A schematic diagram of a redox ion exchange membrane comprising a conductive material comprised of nanostructures of the conductive material, wherein the inorganic microstructure itself is a nanostructure intermixed with the nanostructures of the conductive material.
[0024] Figure 4 It has multiple layers Figure 3-3A Side view of a first embodiment of a redox ion exchange membrane.
[0025] Figure 5 It has multiple layers Figure 3-3AA side view of a second embodiment of a redox ion exchange membrane.
[0026] Figure 6 It shows Figure 3 Flowchart of the operation of the water electrolysis system.
[0027] Fig. 7A yes Figure 3 Schematic diagram of an example of a water electrolysis system utilizing RuO2 in a redox ion exchange membrane, illustrating ion transport in the system.
[0028] Figure 7B yes Figure 3 Schematic diagram of an example of a water electrolysis system utilizing TiO2 in a redox ion exchange membrane, illustrating ion transport in the system.
[0029] Fig. 8A is a scanning electron microscope (SEM) image of the electrochemically pretreated Ti thin layer at a resolution of 2 μm.
[0030] Figure 8B is a SEM image of the electrochemically pretreated Ti thin layer at a resolution of 1 μm.
[0031] Figure 8C is a SEM image of the electrochemically pretreated Ti thin layer after the hydrothermal reaction to form nanowires at a resolution of 2 μm.
[0032] Fig.8D is a SEM image of the electrochemically pretreated Ti thin layer after the hydrothermal reaction to form nanowires at a resolution of 1 μm.
[0033] Fig.9A is a SEM image of titanium felt.
[0034] Fig. 9B yes Fig.9A Energy dispersive spectroscopy (EDS) of titanium felt.
[0035] Fig. 9C is a SEM image of titanium felt at 10 μm resolution after hydrothermal reaction to form nanofilaments.
[0036] Fig.9D yes Fig. 9C EDS of titanium felt.
[0037] Fig.9E is a SEM image of titanium felt at 200 μm resolution after hydrothermal reaction to form nanofilaments.
[0038] Fig. 10A is a SEM image of the titanium filter membrane starting material consisting of sintered micropowder.
[0039] Fig. 10B yes Fig. 10A SEM image of the titanium filter membrane starting material after the hydrothermal reaction to form nanowires.
[0040] Fig.11A is a SEM image of the nickel mesh at 10 μm resolution.
[0041] Fig. 11B yes Fig.11A SEM image of the nickel mesh at 1 μm resolution.
[0042] Fig. 11C is Fig.11A SEM image of Ni(OH)2 / Ni felt at 10 μm resolution after hydrolysis reaction of the Ni mesh to form nanofibers.
[0043] Fig.11D yes Fig. 11C SEM image of the nickel mesh at 1 μm resolution.
[0044] Fig.11E yes Fig. 11C EDS of the nickel mesh.
[0045] Fig. 12A This is the SEM color image of the RuO2 surface.
[0046] Fig. 12B is a color SEM image showing a TiO2 film.
[0047] Fig. 12C is a color SEM image showing the successful formation of RuO2 on the TiO2 film.
[0048] Fig.12D It shows that RuO2 Fig. 12B EDS on the successful formation of TiO2 film.
[0049] Fig.13A is a SEM image of VO2 nanosheets grown on a stainless steel mesh.
[0050] Fig. 13B yes Fig.13A Magnified SEM image of .
[0051] Fig. 13C is an EDS showing the successful formation of VO2 nanosheets on a stainless steel mesh.
[0052] Fig.14 is a SEM image of commercially available Ti fiber felt.
[0053] Fig.15 is a SEM image of RuO2 and TiO2 nanowires generated in situ on the felt.
[0054] Fig.16 Deposition of Ni(OH)2 nanosheets on a Ni filter membrane and electroplating of a RuO2 thin film on a TiO2 film are shown.
[0055] Fig.17 is a representative chronoamperometric response of the Pt anode to water electrolysis using the Ti foil membrane with and without hydrothermal oxidation.
[0056] Fig.18 Representative chronoamperometric responses for water electrolysis in 1.0 M H2SO4 at 2.0 V and 2.5 V using Ti@TiO2 films with and without a RuO2 capping layer sandwiched between the anode and cathode electrodes.
[0057] Fig.19 Typical chronoamperometric responses for water electrolysis at 2.8 V in an H-cell device using Ti@TiO2 membrane.
[0058] The use of the same reference symbols in different drawings indicates similar or identical items. DETAILED DESCRIPTION
[0059] Ion exchange membrane
[0060] refer to Figure 3 , an embodiment of an electrolysis system 2 is shown. A redox ion exchange membrane (RIEM) 4 is located between a cathode 6 and an anode 8. A power source 10 is connected to the cathode 6 and the anode 8. The RIEM 4, the cathode 6, and the anode 8 are placed in a container 12, which can be a standard electrochemical H cell, tank, tube, or other structure. A first compartment 18 of the container 12 contains a first liquid 14, and the cathode 6 is exposed to the first liquid 14 in the first compartment 18. The cathode 6 can form a portion of the wall of the first compartment 18. A second compartment 20 of the container 12 contains a second liquid 16, and the anode 8 is exposed to the second liquid 16 in the second compartment 20. The anode 8 can form a portion of the wall of the second compartment 20. According to some embodiments, the first liquid 14 is different from the second liquid 16. According to other embodiments, the first liquid 14 is the same as the second liquid 16. According to some embodiments, at least one of the first liquid 14 and the second liquid 16 includes H2SO4. According to other embodiments, at least one of the first liquid 14 and the second liquid 16 includes KOH. According to other embodiments, at least one of the first liquid 14 and the second liquid 16 is water. The first liquid 14 and / or the second liquid 16 can be replenished periodically during use. The first liquid 14 and / or the second liquid 16 can be recirculated through the first compartment 18 and the second compartment 20, respectively.
[0061] The cathode 6 and the anode 8 can have conventional structures, and each can be coated with any suitable catalyst. According to some embodiments, at least one of the cathode 6 and the anode 8 is a platinum coil electrode. According to other embodiments, the cathode 6 has a platinum or platinum-based coating thereon. According to other embodiments, the anode 8 has an iridium or iridium oxide coating thereon. According to other embodiments, at least one of the cathode 6 and the anode 8 has an additional or different coating thereon. According to other embodiments, at least one of the cathode 6 and the anode 8 does not have a defined coating thereon.
[0062] RIEM 4 will now be described in more detail. When used in this document, "redox ion exchange membrane" is defined to mean a membrane that undergoes simultaneous reduction and oxidation reactions under the action of an electromagnetic field (e.g., from a cathode and an anode) to produce protons and anions, resulting in these ions permeating the membrane in opposite directions regardless of the transmembrane concentration gradient. Interdependent simultaneous oxidation and reduction reactions are the hallmark of redox reactions. Both the oxidation reaction itself and the reduction reaction itself can be referred to as half reactions because the two half reactions occur together to form a complete redox reaction.
[0063] According to some embodiments, reference Figures 3A-3C , RIEM 4 includes inorganic nanostructures 28 on a conductive material 22. According to some embodiments, the conductive material 22 includes a felt made of or containing at least one transition metal. According to some embodiments, the inorganic microstructure 28 includes nanoparticles, nanofibers, nanotubes, and nanowires. According to some embodiments, the inorganic microstructure 28 includes at least one transition metal oxide. The conductive material 22 can serve as a material on which the inorganic nanostructure 28 is manufactured, deposited, or otherwise placed. The conductive material 22 is part of the RIEM 4, and the fact that the conductive material 22 is conductive does not require that the RIEM 4 as a whole is conductive. In addition, the conductive material 22 does not need to extend across the entire RIEM 4. According to some embodiments, the conductive material 22 need not be a single structure; rather, the conductive material 22 can be a plurality of separate conductive components to which the inorganic nanostructure 28 and / or other redox-active particles such as carbon black are attached. According to some embodiments, the conductive material 22 is at least partially composed of at least one of carbon dots, graphite, graphene, carbon fibers, carbon nanotubes, carbon black, Fe, Co, Ni, Ti, Mn, Zr, Cr, RuO2, IrO2, CrO2, and InSnO2.
[0064] The conductive material 22 may be continuous across the RIEM 4 or may be discontinuous. The conductive material 22 may be a plurality of independent islands across the RIEM 4. The conductive material 22 may be a single material layer, a plurality of adjacent material layers, a crystalline structure, a nanostructure, or any other suitable structure on which the inorganic microstructure 28 may be manufactured, grown, placed, or otherwise prepared. Similarly, the inorganic nanostructure 28 may be continuous across the RIEM 4 or may be discontinuous. The inorganic nanostructure 28 may be a plurality of independent islands across the RIEM 4. The inorganic nanostructure 28 may be a single material layer, a plurality of adjacent material layers, a crystalline structure, a nanostructure, and / or any other suitable structure manufactured, grown, placed, or otherwise prepared on the conductive material 22. Figure 3A , one embodiment of RIEM 4 includes a conductive material 22, which is a film, foil or other generally thin flat layer. Inorganic microstructures 28 are located on both sides of the conductive material 22 layer. Figure 3B Another embodiment of the RIEM 4 includes a conductive material 22 having a branched structure, such as but not limited to titanium. The inorganic microstructure 28 is made of a redox material on the surface of the conductive material 22 in any suitable manner. Figure 3C Another embodiment of the RIEM 4 includes a conductive material 22 comprising nanostructures of a conductive material, wherein the inorganic microstructure 28 itself is a nanostructure that can be mixed with the nanostructures of the conductive material.
[0065] Titanium is a preferred transition metal for use as the conductive material 22, and titanium oxide (TiO2) is a preferred transition metal oxide for use as the inorganic microstructure 28. However, any other transition metal or metals may be used in place of or in addition to titanium, including scandium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thallium, ytterbium, lutetium, hafnium, tantalum, tungsten, rhenium, osmium, iridium, platinum, gold, mercury, actinium, thorium, protactinium, uranium, neptunium, plutonium, americium, curium, berkelium, californium, einsteinium, fermium, mendelevium, nobelium, lawrencium, tantalum, tungsten, rhenium, osmium, iridium, platinum, gold, mercury, actinium, thorium, protactinium, uranium, neptunium, plutonium, americium, curium, berkelium, californium, einsteinium, fermium, mendelevium, nobelium, lawrencium, (seaborgium), (hassium), In addition, instead of or in addition to titanium oxide, any other oxide or oxides, chalcogenides or chalcogenides of these transition metals may be used, such as but not limited to FeO, Fe2O3, FeS, CoS, CoO, NiO, MnO2, ZrO2 and / or Cr2O3. In addition, instead of or in addition to titanium oxide, any salt of these transition metals may be used, such as but not limited to Fe4[Fe(CN)6]3, CoTiO2 and / or LiSeO4.
[0066] According to some embodiments, at least a portion of the conductive material 22 of the RIEM 4 is made of a non-metallic material. Such non-metallic materials may be at least one of carbon materials (such as but not limited to carbon dots, graphite, graphene, carbon fibers, carbon nanotubes, and / or carbon black), sulfur, arsenic, selenium, boron, phosphorus, oxides of the aforementioned materials (such as but not limited to A2SO3, SeO2, As2O5, B2O3, and / or P2O5), and salts of the aforementioned materials (such as but not limited to NaAsO2, Na2SeO3, LiPO4, and / or NaBO3).
[0067] In certain embodiments, a redox active coating or layer is deposited on the conductive material 22 and / or the inorganic nanostructures 28. Such a redox active coating or layer can be the same material or two different materials. In rare cases, after applying a bias, a redox active layer such as underpotential deposited hydrogen (denoted as H upd ) layer may be formed on one side of a substrate (eg, a metal film). upd layer can diffuse through the substrate to the other side. In rare cases, the surface H upd The layers can be considered as redox active materials. In addition, redox active organic or polymeric materials can be added as co-catalysts to improve the rate of ion transport and the overall performance.
[0068] At least one organic substance, such as a small molecule or polymer, may be applied to the conductive material 22 and / or the inorganic nanostructures 28, and / or may be applied to a portion of another portion of the RIEM 4 and / or form a portion thereof as a coating. The use of at least one organic substance as a coating may be used to bond layers of the RIEM 4 (as described below), to adjust affinity for water, such as the local hydrophilic or hydrophobic nature of the RIEM 4, and / or to create mechanical flexibility of the RIEM 4. Redox-active polymers and macromolecules (e.g., (poly)quinones, polyimides, and polypyrroles), hydrophilic and / or hydrophobic additives (e.g., surfactants, PTFE nanoparticles, and zwitterionic compounds), and crosslinking agents (e.g., glutaraldehyde, silica gel, and interfacial polymerization) may be usefully applied to the conductive material 22.
[0069] RIEM 4 can be a single structure or can be composed of two or more layers. Figure 4 , RIEM 4 includes a first layer 24 and a second layer 26. As in Figure 4 As seen in FIG. 1 , the first layer 24 extends across substantially all of the second layer 26. Also refer to Figure 5 , the second layer 26 extends across only a portion of the first layer 24. The second layer 26 can be a plurality of separate strips that span the first layer 24, or can have any other suitable shape. More layers can be used as desired. The use of multiple layers 24, 26 can enhance certain properties of the redox active membrane, such as the capacity and rate of ion transfer.
[0070] According to some embodiments, one of the layers 24, 26 of the RIEM 4 is a solid layer. According to some embodiments, the solid layer is a foil composed of a transition metal or a transition metal oxide. According to some embodiments, the solid layer extends across the entire RIEM 4. According to other embodiments, the solid layer extends across a portion of the RIEM 4. The use of one or more solid layers in the RIEM 4 improves the separation efficiency across the redox-active membrane, for example by minimizing crossover effects in a fuel cell. According to other embodiments, the solid layer 24 is omitted from the RIEM 4.
[0071] According to some embodiments, a liquid or gel is mixed with the RIEM 4 to create a pseudo solid electrolyte. According to other embodiments, the RIEM 4 may be completely solid, in which case the RIEM is a solid electrolyte.
[0072] run
[0073] Also refer to Figure 6 , describes the operation 100 of the electrolysis system 2 using the RIEM 4. First, at box 102, the electrolysis system 2 is prepared. The first compartment 18 is filled to an appropriate level with the first liquid 14, and the second compartment 20 is filled to an appropriate level with the second liquid 16. The first liquid 14 and the second liquid 16 are heated to an operating temperature. Any other preparations required for safe operation of the electrolysis system 2 are also performed.
[0074] Next, at box 104, power is applied to the cathode 6 and anode 8. The amount of voltage and current applied depends on the properties of the first liquid 14 and the second liquid 16 and the properties of the RIEM 4. The proton transfer capability of the RIEM 4 depends on its relative potential, so that the voltage applied to the cathode 6 and anode 8 is greater than the potential to cause proton transfer. Examples are provided below. The power applied to the cathode 6 and anode 8 generates an electromagnetic field that is applied to the RIEM 4.
[0075] Next, at block 106, as a result of applying power to the cathode 6 and anode 8 and applying an electromagnetic field to the RIEM 4, protons (hydronium ions) and anions (OH - ions) are simultaneously transferred across the RIEM 4. As a result of the electromagnetic field applied to the RIEM 4, electrons are also transferred across the RIEM 4. The direction of ion movement across the RIEM 4 is not driven by the concentration gradient across the RIEM 4. Instead, the electrochemical driving force (i.e., the relative voltages with respect to the cathode and anode) determines the direction of transfer and causes the ions to permeate and pass through the RIEM 4. In addition, the electron transfer across the RIEM 4 is driven by the bias potential across the RIEM 4, so that a minimal iR drop can be achieved. For example, when using the RIEM 4, a lower OH - Concentrated catholyte (i.e. acidic solution) and high OH - In the water electrolysis method with an anolyte (i.e., alkaline solution) of high concentration, OH - Ions are transferred from the cathode side to the anode side by an electrochemical driving force.
[0076] According to some embodiments, during the operation of RIEM 4, OH - Instead, the redox-active species in RIEM 4 are oxidized and / or reduced, absorbing or releasing OH - Similarly, according to some embodiments, during the operation of RIEM 4, H + In this way, the RIEM 4 can operate for a considerable period of time without replenishing the electrolyte of the first liquid 14 and / or the second liquid 16. In addition, the operation of the RIEM 4 does not utilize ion transport across the RIEM 4. Therefore, the RIEM 4 can be solid or can contain solid components without degrading the operation of the RIEM 4.
[0077] As an example, refer to Fig. 7A , the RIEM 4 is placed between a first liquid 14 and a second liquid 16, both of which are 1.0M H2SO4 solutions in water. It should be understood that other solutions may be used instead of or in addition to the 1.0M H2SO4 solution in water, such as HClO4 and H3PO4 solutions in water, alone or in combination. The concentrations of these electrolytes in water may also vary from a 1.0M solution. The RIEM 4 of this example includes a conductive material 22 composed of Ti and an inorganic microstructure 28 composed of RuO2, and operates by the following reaction:
[0078] - On one side of RIEM 4, RuO2+H + +e -→RuOOH (i.e. RuO2 is oxidized, and at the same time H + is absorbed).
[0079] - On the opposite side of RIEM 4, RuOOH → RuO2 + H + +e - (i.e. Ru is reduced, and at the same time H + was released).
[0080] It should be understood that in the above example, one reaction occurs on one side of RIEM 4, while the opposite reaction simultaneously occurs on the opposite side of RIEM 4. Ti in both TiO2 and TiOOH substances changes its chemical valence, i.e., Ti in RIEM 4 participates in the redox reaction. - It is neither reduced nor oxidized, although it participates in the redox reaction.
[0081] As another example, refer to Figure 7B , the RIEM 4 is placed between a first liquid 14 and a second liquid 16, both of which are solutions of 1.0M KOH in water. It should be understood that other solutions may be used instead of or in addition to the 1.0M KOH solution in water, such as solutions of LiOH, NaOH, RbOH, and CsOH in water, alone or in combination. The concentration of these electrolytes in water may also vary from a 1.0M solution. The RIEM 4 of this example includes a conductive material 22 composed of Ti and an inorganic microstructure 28 composed of RuO2, and operates by the following reaction:
[0082] - On one side of RIEM 4, TiO2+H2O+e - →TiOOH+OH - (i.e. TiO2 is reduced and at the same time OH - was released).
[0083] - In the RIEM 4 prediction, TiOOH+OH - →TiO2+H2O+e - (i.e. Ti is oxidized and at the same time OH - is absorbed).
[0084] It should be understood that in the above example, one reaction occurs on one side of RIEM 4, while the opposite reaction simultaneously occurs on the opposite side of RIEM 4. Ti in both TiO2 and TiOOH substances changes its chemical valence, i.e., Ti in RIEM 4 participates in the redox reaction. - It is neither reduced nor oxidized, although it participates in the redox reaction.
[0085] As above about Figure 7A-7B As described above, the cathode and anode reactions are coupled to the oxidation and reduction at the RIEM 4, respectively. The redox reaction at the RIEM 4 is easily reversible. In addition, within the RIEM 4, spontaneous chemical reactions occur to balance chemical energy, cyclically transferring the generated ions. That is, in operation, the RIEM 4 simultaneously reduces and oxidizes the target ions (e.g., H) on both sides of the RIEM 4 under an electric field. + and OH - ). When one reaction absorbs ions from its surroundings, the other reaction releases the same ions, thereby causing redox driven ion transport (RDIT), which drives ion movement relative to the RIEM 4. That is, applying power to the cathode 6 and the anode 8 induces simultaneous reversible reduction and oxidation reactions on opposite sides of the redox ion exchange membrane 4, thereby releasing H on one side of the redox ion exchange membrane 4. + .
[0086] Next, return Figure 6 At box 108, in the first compartment 18 containing the cathode 6, the protons that have migrated through the RIEM 4 gain electrons to form hydrogen. This electron acquisition occurs at the cathode 6, where the electrons react with H + The ions combine to form hydrogen gas.
[0087] At the end of the run 100 , at box 110 , the hydrogen gas formed in the first compartment 18 is collected and stored for later use.
[0088] Fuel Cells
[0089] It is known in the art that electrolysis systems can be operated in reverse as fuel cells. Therefore, RIEM 4 is suitable for use in fuel cells and electrolysis systems for producing hydrogen. For example, a RIEM 4 using a conductive material 22 composed of Ti and an inorganic nanostructure 28 composed of TiO2 can be used in an alkaline fuel cell system. The RIEM 4 can be used with a first liquid 14 and a second liquid 16, both of which are aqueous solutions with 1.0M KOH, using H2 and O2 feed gases. Instead of a cathode 6 and an anode 8, the fuel cell includes two electrodes on opposite sides of the RIEM 4. H2 is oxidized at the negative electrode, while O2 is reduced at the positive electrode, outputting voltage and current via the electrodes. RIEM 4 is biased relative to the two electrodes. Therefore, TiO2 / Ti will be reduced near one side of the RIEM 4 facing the negative electrode, while releasing OH- ions. Therefore, TiO2 / Ti (reduced form) will be oxidized near the other side of the RIEM 4, absorbing OH- ions from its environment.
[0090] In the case of using RIEM 4 in a fuel cell having two electrodes, according to some embodiments, at least one electrode is at least partially made of a noble metal. "Noble metal" refers to any metal or semi-metal element that does not react with a weak acid and releases hydrogen in the process, which is a group including the six platinum group metals (platinum, gold, ruthenium, rhodium, palladium, osmium and iridium), copper, mercury, technetium, rhenium, arsenic, antimony, bismuth, polonium and silver.
[0091] Example
[0092] Example 1
[0093] To demonstrate the principle of RIEM 4, experiments were conducted using titanium and titanium oxide. In Example 1, a commercially available titanium film with a measured thickness of 12.5 μm was used as the material, the surface of which is usually covered with an oxide layer (TiO2) on the scale of a few nanometers. In order to increase the amount of surface oxide, a titanium film disk with a measured diameter of 1.0 inch was treated in a two-step process. First, the titanium film disk was electrochemically oxidized at 20.0 V for 4.0 hours in a mixed solution of 1.0 M NH4Cl and 5.0 M KOH to roughen the surface, thereby increasing the effective surface area ( ) for the subsequent formation of TiO2 nanostructures. Figures 8A-8B Then, the pretreated film was subjected to a hydrothermal reaction in 10.0 M NaOH at 130° C. for 24 hours. Figure 8C and 8D shows additional layers on the titanium substrate. In addition, higher magnification images ( Fig.8D ) shows that the additional layer comprises nanowires that are tightly entangled with each other.
[0094] Example 2
[0095] As another example to verify the principle of redox active membrane, commercial titanium felt was cleaned by ultrasonic bath and then further cleaned in a solution of acetone, ethanol and deionized water. As in Example 1, the surface of each titanium fiber ( Fig.9A ) are transformed into TiO2 nanofilaments that are tightly entangled with each other. Fig. 9C and 9E Shown is a SEM image of the titanium felt after TiO2 nanofilament production. Fig. 9B is the EDS of the commercial Ti felt before treatment. Fig.9D is the EDS of the treated Ti felt, confirming the presence of TiO2 nanowires.
[0096] Example 3
[0097] The same procedure as in Example 2 was used to transform a commercially available titanium filter membrane into a nanoporous TiO2 / Ti filter membrane. The titanium filter membrane starting material consisted of sintered micropowder ( Fig. 10A ). Comparison shows that the final TiO2 / Ti filter membrane is composed of TiO2 nanowires on a metallic Ti skeleton ( Fig. 10B ).
[0098] Example 4
[0099] In another example, RIEM 4 containing Ni(OH)2 was grown on a nickel mesh by an enhanced hydrolysis method at 90°C in an aqueous solution containing 50M Ni(NO3)2 and 1.0M urea. The starting material of the commercially available nickel mesh includes interconnected nickel fibers ( Figures 11A-11B ). The hydrolysis of the Ni mesh produced the final Ni(OH)2 / Ni felt film, in which the individual Ni fibers were conformally and uniformly modified by Ni(OH)2 nanosheets ( Figures 11C-11D ). Fig.11E yes Figures 11C-11D EDS spectrum of the final Ni(OH)2 / Ni felt film.
[0100] Example 5
[0101] TiO2 / Ti RIEM 4 was prepared using the same method as in Examples 1, 2 and 3 above. RuO2 was electrochemically deposited on the prepared TiO2 / Ti in an electrolytic cell containing 0.5M H2SO4 and 50mM RuCl3. The electrodeposition was achieved at room temperature using a three-electrode system. Platinum foil and Ag / AgCl electrodes were used as counter electrode and reference electrode, respectively. The electrodeposition used a chronoamperometric step function, i.e. -0.6V for 5 minutes and then -0.4V for 0.5 minutes. All potentials were quoted for the Ag / AgCl reference electrode. The successful formation of RuO2 on the TiO2 / Ti film was confirmed by SEM color images and EDS ( Figures 12C-12D ). Figures 12A-12B Color maps of Ru alone and Ti alone are shown, respectively.
[0102] Example 6
[0103] VO2 nanosheets were grown on stainless steel (sst) mesh by an electrodeposition method using a three-electrode system at room temperature to form VO2 / stainless steel (sst) membranes for potassium batteries. Platinum foil and Ag / AgCl electrodes were used as counter and reference electrodes, respectively. The electrolytic cell consisted of 0.5M H2SO4 and 50mM VO·SO4·H2O (vanadium (IV) sulfate oxide). Electrodeposition occurred at -0.75V relative to Ag / AgCl (filled with 3M KCl) for different lengths of time. The results were obtained by SEM ( Figures 13A-13B ) and EDS( Fig. 13C )The VO2 / sst film was characterized.
[0104] Other embodiments
[0105] To further demonstrate the concept and feasibility of RIEM 4, a nanoporous membrane consisting of nanoscale metal oxides surrounding a metal skeleton was produced. Fig.14 , a SEM image of a commercially available Ti fiber felt can be seen. A representative energy dispersive spectrum (EDS) of the Ti fiber felt is also shown in Fig.14 Reference Fig.15 , showing SEM images of RuO2 and TiO2 nanowires generated in situ on the felt. A representative energy dispersive spectrum (EDS) of the material is also shown in Fig.15 Commercially available Ti felt was hydrothermally reacted in aqueous solution to produce a redox-active TiO2 nanofilament layer on the individual fibers of the TiO2 felt. These TiO2 nanofilaments were tightly entangled on the individual Ti fibers and interconnected between adjacent Ti fibers, forming a nanoporous structure. Fig.16 , showing the deposition of Ni(OH)2 nanosheets on a Ni filter membrane and the electroplating of a RuO2 thin film on a TiO2 film.
[0106] Will be like Fig.16 RIEM 4, comprising RuO2 and TiO2 nanowires on Ti fiber felt, in the configuration shown in FIG, is sandwiched between two identical Pt electrodes (anode and cathode, respectively) in an H-shaped cell. The two-electrode system is used for water electrolysis in 1.0 M KOH solution and 1.0 M H2SO4 solution. RIEM 4 is conductive, so it can be used as a bipolar electrode to decouple the anode and cathode, and also to shuttle ions without electrochemical reactions on either side.
[0107] From thermodynamic calculations, it is known that in order to perform water splitting at 25°C, the electrolysis voltage is 1.48 V. Therefore, if the system of the present invention is mistakenly regarded as two electrochemical cells connected in series and separated by a bipolar electrode, a voltage of 2.96 V (i.e., 2 times 1.48 V) would be the minimum requirement to anchor the water splitting reaction. However, referring to Figures 11-12, this situation is experimentally ruled out because the following voltages were applied, all of which were below 2.96 V: 2.0 V, 2.2 V, 2.5 V, and 2.8 V.
[0108] Solid titanium foil with a measured thickness of 0.5 mil (12.5 μm) was hydrothermally oxidized in a 10 M NaOH solution at high temperature. The formation of surface TiO2 was confirmed by SEM / EDS, and permeation experiments showed that the foil remained solid and waterproof. As a result, RIEM 4 was produced. Figure 11 shows a representative chronoamperometric response of Pt anode 8 to water electrolysis using Ti foil membranes with and without hydrothermal oxidation. After applying voltage to the two Pt electrodes 6, 8, a Faradaic current response associated with the hydrolysis of water was observed; this was true for both the original membrane and the oxidized membrane. Therefore, ion exchange through the membrane occurred, forming a closed internal loop of charge movement to couple the anode and cathode reactions. This observation is counter-intuitive because the waterproof, solid characteristics of RIEM 4 eliminate mass diffusion across RIEM 4 caused by concentration gradients. Instead, this ion exchange process is associated with the redox reaction of TiO2 that absorbs and desorbs hydroxide ions. When voltage is applied to the two Pt electrodes 6, 8, the RIEM 4 sandwiched therebetween conducts electricity and becomes bipolarized; that is, it acts as an anode to couple with the Pt cathode 6 through its oxidation, while simultaneously acting as a cathode to couple with the Pt anode 8 through its reduction. On the other hand, due to its high conductivity, the entire RIEM 4 tends to carry objects of comparable potential, which causes the oxidized and reduced forms of titanium to self-discharge until equilibrium is achieved. In summary, the cycle of redox reactions of titanium or its oxide absorbs hydroxide ions (OH-) from one side of the RIEM 4 while releasing OH- to the other side of the RIEM 4, creating an efficient ion transport pathway. This working mechanism was further investigated by control experiments, in which the original membrane and the oxidized RIEM 4 were used in parallel for comparison. Under the same conditions, the oxidized RIEM 4 enabled water electrolysis to proceed at a much higher efficiency than the original membrane, as evidenced by the Faradaic response of 244.3 μA (blue curve) compared to 22.4 μA (red curve) for a voltage of 2.2 V (Figure 11). When the two films were compared at a voltage of 2.8 V, the same relative kinetics were obtained.
[0109] The important role of redox active species in the transport of protons was investigated by controlled experiments of water electrolysis in acidic media, in which Ti@TiO2 RIEM 4 with and without additional deposits of RuO2 were investigated in parallel. The measured thickness of the Ti@TiO2 membrane was 0.8 mm and had a nanoporous structure. Figure 12 shows representative chronoamperometric responses to water electrolysis at 2.0 V and 2.5 V in 1.0 M H2SO4, using Ti@TiO2 membranes with and without a RuO2 capping layer sandwiched between the anode and cathode electrodes. The electrochemical configuration with the Ti@TiO2 membrane alone (without RuO2) was unable to anchor the water electrolysis reaction at 2.0 V or 2.5 V (red curves in Figure 12). Due to the special physical structure of the membrane (thickness of 0.7 mm and pore size of tens of nm), this failure can be translated into a functional impairment of the membrane in ion conduction, thereby decoupling the electrochemical reactions at the two electrodes. This situation would be exacerbated if the capping layer was deposited on the surface of the Ti@TiO2 and / or in the membrane. However, Figure 12 (blue curve) reproduces a significant Faradaic response that is causally related to water electrolysis under controlled conditions. The comparison shows that a closed internal circuit is formed by ion conduction through RuO2 / Ti@TiO2. This observation seems counterintuitive because RuO2 deposits on / in Ti@TiO2 are expected to further disrupt ion conduction by acting as an additional barrier and / or reducing the pore size. Therefore, RuO2 / Ti@TiO2 conducts ions through a working mechanism other than mass diffusion, migration, or convection. As discussed above for anionic membranes, the components in RuO2 / Ti@TiO2 work synergistically on the basis of the redox reaction involved in the protons of RuO2 to transport ions through RIEM 4. It is worth noting that although the TiO2 component has reversible redox properties in acidic media, it was found to be unsuitable for ion conduction alone under our experimental conditions because its redox potential exceeds the water splitting voltage. Relatively speaking, TiO2 is nanosized and can act as a high surface area carrier for RuO2 to achieve the desired ion transport.
[0110] Based on the above experiments, Ti@TiO2 and RuO2 / Ti@TiO2 were selected as anion conductive membranes and cation conductive membranes, respectively. A commercially available titanium fiber felt disk (porosity 53%-56%) with a measured diameter of 25 mm and a thickness of 0.25 mm was subjected to hydrothermal reaction in a PTFE-lined autoclave reactor for 24 hours. The titanium surface was oxidized into titanium oxide nanowires surrounding each titanium fiber; the entire disk was transformed into a nanoporous structure.
[0111] To evaluate the performance of the Ti@TiO2 membrane, platinum coil electrodes were placed in an H-shaped container separated by the Ti@TiO2 membrane. The chronoamperometric response to a predetermined voltage in water electrolysis was recorded and compared with the results obtained using a FUMATECH BWT GmbH, Bietigheim-Bissingen, Germany Figure 13 shows that in the H-cell device with Ti@TiO2 membrane prepared as above, compared with the device using Typical chronoamperometric response for water electrolysis at 2.8 V compared to the same experimental setup of a Ti@TiO2 membrane from a Ti filter membrane. The membrane consisting of TiO2 nanostructures on a Ti filter membrane (1.0 μm porosity, 0.7 mm thickness) is referred to as Ti@TiO2 membrane and exhibits similar The AEM membranes of the brands have comparable internal resistances, as evidenced by their overlapping current versus time curves (red and purple curves). After reducing the membrane thickness to 0.25 mm, the membrane consisting of TiO2 nanostructures on Ti felt, called Ti@TiO2 felt, evoked a current response that was three times greater than that using Ti@TiO2 membrane. Due to the thickness-dependent electrochemical impedance, the electrode reaction kinetics are enhanced. Considering the negligible barrier for electrons shuttling through the titanium filter and felt mesh, the membrane thickness is likely to define the ion transport rate across the membrane and, therefore, the overall kinetics of the entire redox reaction involving ions (i.e., ion transport kinetics). With NATION TM The RuO2 / Ti@TiO2 membranes working in acidic media have similarly higher ion transfer kinetics compared to the 212 brand membranes. Figure 10 shows the histograms of hydrogen production rates for different membranes in 1.0 M KOH at 2.8 V and in 1.0 M H2SO4 at 2.5 V. Six times higher hydrogen production rates were achieved using our Ti@TiO2 membranes in H2SO4 relative to the corresponding commercial membranes, while nearly 25% higher hydrogen production rates were achieved for RuO2 / Ti@TiO2 in KOH.
[0112] The use of RIEM 4 in a method for producing hydrogen has been described above. It will be appreciated that RIEM 4 may be used in other applications. As one application, RIEM 4 may be used to separate electrodes and / or conduct ions in a fuel cell; a fuel cell is essentially the reverse process of the above-described method for producing hydrogen. As another application, RIEM 4 may be used in a metal air / oxygen battery, such as a zinc-air battery. As another application, RIEM 4 may be used in a lithium-ion battery. As another application, RIEM 4 may be used in an electrochemical supercapacitor or pseudo-supercapacitor.
[0113] As used in this document, and as commonly used in the art, approximate terminology, including the words "substantially" and "approximately," are defined to mean normal variations associated with accuracy, precision, and / or tolerances in dimensions, measurements, and physical properties of items and processes in the physical world.
[0114] Although the present invention has been described in detail, it is obvious to those skilled in the art that various changes and modifications may be made and equivalents may be adopted without departing from the present invention. It should be understood that the present invention is not limited to the details of construction, arrangement of components and / or methods described in the above description or shown in the accompanying drawings. The statements in the abstract of this document and any summary statements in this document are merely exemplary; they are not and cannot be interpreted as limiting the scope of the claims. In addition, the drawings are merely exemplary and not restrictive. The topic headings and subheadings are for the convenience of the reader only. They should not and cannot be interpreted as having any substantive meaning, implication or interpretation, nor should they and cannot be regarded as indicating that all information related to any particular subject matter exists under or is limited to any particular heading or subheading. Therefore, except in accordance with the following claims and their legal equivalents, the present invention will not be restricted or limited.
Claims
1. A redox ion exchange membrane comprising: Conductive materials; and A redox active material is associated with the conductive material, the redox active material having reversible oxidation and reduction properties.
2. The redox ion exchange membrane of claim 1, wherein the redox active material comprises an inorganic nanostructure. 3 . The redox ion exchange membrane according to claim 2 , wherein the inorganic nanostructure is an oxide of a material constituting the conductive material.
4. The redox ion exchange membrane of claim 2, wherein the conductive material comprises two opposing surfaces, and wherein the inorganic nanostructure comprises at least one layer on at least one of the surfaces of the conductive material. 5 . The redox ion exchange membrane of claim 1 , wherein the inorganic nanostructure comprises at least one of nanoparticles, nanofibers, nanotubes, and nanowires.
6. The redox ion exchange membrane of claim 1, wherein the conductive material is porous.
7. The redox ion exchange membrane of claim 1, wherein the conductive material comprises at least one transition metal. 8 . The redox ion exchange membrane according to claim 1 , wherein the conductive material comprises at least one of a transition metal oxide, a transition metal sulfide, an alkali metal salt, and a transition metal salt.
9. The redox ion exchange membrane of claim 1, wherein the conductive material comprises titanium felt, and wherein the inorganic nanostructure comprises titanium nanowires at least partially covered with titanium oxide.
10. The redox ion exchange membrane of claim 1, wherein the conductive material is at least one of carbon dots, graphite, graphene, carbon fibers, carbon nanotubes, carbon black, Fe, Co, Ni, Ti, Mn, Zr, Cr, RuO2, IrO2, CrO2, and InSnO2.
11. A hydrogen production device, comprising: cathode; an anode; and A redox ion exchange membrane is disposed between the cathode and the anode, wherein the redox ion exchange membrane has a first surface and a second surface opposite to the first surface. 12 . The hydrogen production apparatus according to claim 11 , wherein the cathode is immersed in a solution containing water, and wherein the solution containing water is in contact with the first surface of the redox ion exchange membrane. 13 . The hydrogen production apparatus according to claim 11 , wherein the anode is immersed in a solution containing water, and wherein the solution containing water is in contact with the second surface of the redox ion exchange membrane. 14 . The hydrogen production device according to claim 11 , wherein the cathode and the anode each comprise at least one of a transition metal and an alloy of the transition metal.
15. A fuel cell device comprising: a first electrode; a second electrode; and A redox ion exchange membrane is located between the first electrode and the second electrode, wherein the redox ion exchange membrane has a first surface and a second surface opposite to the first surface. 16 . The fuel cell device according to claim 15 , wherein the first electrode and the second electrode are immersed in a solution containing water, and wherein the solution containing water is in contact with the first surface and the second surface of the redox ion exchange membrane. 17 . The fuel cell device according to claim 15 , wherein the first electrode and the second electrode each comprise at least one of a noble metal and an alloy of the transition metal.
18. A method for producing hydrogen, the method comprising: providing a cathode, an anode, and a redox ion exchange membrane located between the cathode and the anode, the redox ion exchange membrane having a first surface and a second surface opposite to the first surface; and applying power to the cathode and the anode; wherein the applying induces simultaneous reversible reduction and oxidation reactions on opposite sides of the redox ion exchange membrane, thereby releasing H on one side of the redox ion exchange membrane + .
19. The method of claim 16, wherein the simultaneous reversible reduction and oxidation reactions occur on opposite sides of the redox ion exchange membrane regardless of a concentration gradient across the redox ion exchange membrane.
